The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/gcb.15766
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐associated decline of body condition in a fossorial salamander

Abstract: Global climate change is unequivocal, and rates of observed and predicted temperature increases are greater at higher latitudes (Intergovernmental Panel on Climate Change, 2014). High-and mid-latitude regions have experienced rapid environmental change over the past half-century, including increases in mean air and surface temperature, extreme high temperature events, decreases in the number of frost-free days, and decreases in ice cover (Bartolai et al., 2015;Cohen et al., 2014). The short post-glacial histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 118 publications
(129 reference statements)
1
21
0
Order By: Relevance
“…Our study measured the consequences for salamanders from a single pond; therefore, our findings may not represent the consequences for populations locally adapted to warmer or cooler ponds. However, a recent observational study in a closely related species ( Ambystoma maculatum ) found results consistent with ours; a slight increase in summer temperature significantly explained, in part, a decline in body condition in adults over 12 years, but temperature did not explain the variation in reproductive output (Moldowan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Our study measured the consequences for salamanders from a single pond; therefore, our findings may not represent the consequences for populations locally adapted to warmer or cooler ponds. However, a recent observational study in a closely related species ( Ambystoma maculatum ) found results consistent with ours; a slight increase in summer temperature significantly explained, in part, a decline in body condition in adults over 12 years, but temperature did not explain the variation in reproductive output (Moldowan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…While the sensitivity of amphibians to climate change is well‐documented and many species are predicted to endure negative fitness consequences (e.g. Caruso et al, 2015; Moldowan et al, 2021; Reading, 2007), animal responses to climate change are highly trait‐dependent (Pacifici et al, 2017). Even though trait‐based studies indicate that climate change will favour certain life history strategies, we lack an understanding of how climate change will alter the specific mechanisms that maintain the trade‐offs underlying life history diversity (Both & Visser, 2005; Lancaster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on two fitness parameters linked to amphibian life history that are impacted by climate: breeding state and body condition. Breeding and phenology are well established as being linked to temperature and precipitation (Ficetola & Maiorano, 2016; Reading, 1998; Todd et al, 2011), while numerous studies have documented climate‐induced increases and decreases of population‐level body size (Caruso et al, 2015; Moldowan et al, 2021; Reading, 2007). However, very little is known about how climate mechanisms influence fitness trade‐offs, and whether climate mechanisms are responsible for maintaining phenotypic diversity and polyphenisms (Merilä & Hendry, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings highlight the potential of individual response metrics in species monitoring and conservation. The explicit links between herpetofauna body condition, demographic impacts and population size remain understudied (Lannoo & Stiles, 2017; Moldowan et al, 2022; Reading, 2007) and more long‐term research is needed to assess these links. Moreover, research should simultaneously measure individual, population and community metrics to assess how different response metrics relate to one another.…”
Section: Future Directionsmentioning
confidence: 99%
“…Our findings highlight the potential of individual response metrics in species monitoring and conservation. The explicit links between herpetofauna body condition, demographic impacts and population size remain understudied (Lannoo & Stiles, 2017;Moldowan et al, 2022;Reading, 2007)…”
Section: Future Direc Tionsmentioning
confidence: 99%